(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this study was to assess the treatment results following endodontic therapy of teeth filled with gutta-percha A total of 340 patients were used in this study referring to Al-Mustansirya University, 400 periapical radiographs of previously endodontic treated teeth were evaluated from patients were aged from 19-49 years old selected amongst subjects referred to Al- Mustansirya dental collage, these patients had been root filled for 12 months or greater. After samples selection, Radiographic examination was performed using the parallel technique with one periapical radiograph was taken for each tooth. Standardized exposure processing was used in order to obtain optimal diagnostic quality of the radiographs. Radiographs were assigned according to patient’s sex and age, time elapsed since placement of the root fillings, distance of root filling from radiographic apex which measured directly from the radiographic categorized according to whether the root filling was less than 2 mm from the radiographic apex , or over filled teeth also pain and presence or absence of radiolucency was recorded. In conclusion, teeth with root canal fillings material placed to within 2 mm of the radiographic apex were associated with higher success rates than fillings that were 2 mm or greater from radiographic apex.